The Compilation of Islamic Law in Indonesia: A Critical Analysis of Its Legal Position, Substantive Limitations, and Reform Prospects - Silvia Marlina; Rizki Eka Putra; Budi Budi; Yuharniza Yuharniza; Moh. Arief Hidayat; Sri Wahyuni; Desi Asmaret (Lembaga Penelitian, Penerbitan dan Pengabdian Masyarakat (LP3M) IAI Al Urwatul Wutsqo - Jombang, 2026)
The Compilation of Islamic Law (Kompilasi Hukum Islam/KHI) is one of the most significant instruments in the development of Islamic law in Indonesia, particularly in the areas of marriage, inheritance, and waqf. Although it has served as the primary legal guideline for Religious Courts since its promulgation through Presidential Instruction No. 1 of 1991, the KHI continues to generate debates regarding its formal legitimacy, substantive provisions, and relevance to contemporary social developments. This study aims to critically examine the strengths, weaknesses, and reform directions of the KHI within the framework of Indonesia’s national legal system. The research employs a library research method with a descriptive-analytical approach. Data sources consist of primary legal materials, including the KHI and related regulations, as well as secondary materials such as books, journal articles, and previous scholarly studies. Data were analyzed through a normative assessment of the KHI’s legal position, functions, implementation, and challenges in Islamic family law practice. The findings indicate that the principal strength of the KHI lies in its ability to promote legal uniformity, simplify diverse fiqh opinions into operational legal provisions, and strengthen legal certainty within Religious Courts. However, the KHI also faces formal and substantive limitations, including its relatively weak legal status and its insufficient responsiveness to issues of gender justice, child protection, legal pluralism, and contemporary family dynamics. Therefore, KHI reform should be conducted through a participatory and maqāṣid al-syarī‘ah-based approach that emphasizes substantive justice and social responsiveness